Potassium fertilization to augment growth, yield attributes and yield of dry direct seeded basmati rice (Oryza sativa) - S, VIJAYAKUMAR; KUMAR, DINESH; SHARMA, V K; SHIVAY, Y S; ANAND, ANJALI; P, SARAVANANE; JINGER, DINESH; SINGH, NAIN (The Indian Journal of Agricultural Sciences, 2019)
The effect of potassium (K) application based on 4R stewardship (right rate, time, method, and source) on growth, yield attributes and yields of dry direct seeded basmati rice (Oryza sativa L.) was evaluated during rainy (kharif) season of 2015 and 2016 at IARI, New Delhi. Application of recommended dose of K (60 kg/ha), half as basal and remaining half at panicle initiation (PI) stage increased the grain (5.4 t/ha) and straw yields (7.65 t/ha) by 10 and 4% respectively, over applying the full dose as basal. A strong, positive and significant correlation was observed between yield attributes [panicle weight (r2=0.79), panicle length (r2=0.83), fertility % (r2=0.84)] and yield of dry direct seeded basmati rice. Similarly, positive and significant correlation was observed between leaf area index at 60 DAS (r2=0.73) & 90 DAS (r2=0.91) and dry matter production. The two foliar sprays of 2.5% potassium nitrate (1st at active tillering, and 2nd at panicle initiation) increased fertility (83.5%) and grain yield (4.3 t/ha) by 6% and 8% respectively, over control. However, the combined application of foliar sprays and two split application of recommended dose of K showed non-significant effect on growth, yield and yield attributes. Thus, to obtain higher yield in dry direct seeded basmati rice, application of 60 kg/ha, half as basal and remaining half at panicle initiation (PI) is recommended.